New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera - Ingrisch, Sigfrid (Zootaxa, 2018)
New records of Gryllacrididae from South East Asia to New Guinea are reported, new taxa are described and type specimens from European collections redescribed. The wing venation of the tegmina and its variation within the family is discussed. A new key to the 50 genera and subgenera of Gryllacrididae occurring in the area from South East Asia to New Guinea is provided. Six genera and two subgenera are introduced as new: Angustogryllacris gen. nov., Minigryllacris gen. nov., Monseremus gen. nov., Siamgryllacris gen. nov., Paraneanias gen. nov., Plexigryllacris gen. nov., Pseudasarca subgen. nov. of Asarcogryllacris Karny, 1937, Xiphilarnaca subgen. nov. of Metriogryllacris Karny, 1937. Two genera Gigantogryllacris Karny, 1937 and Pardogryllacris Karny, 1937 are reduced to subgeneric status under Gryllacris Audinet-Serville, 1831 and one monotypic genus Cyanogryllacris Karny, 1937 is synonymised with Capnogryllacris Karny, 1937. 70 species and nine subspecies are described as new: Eugryllacris gandaki sp. nov., Eugryllacris guomashan sp. nov., Eugryllacris crassicauda sp. nov., Eugryllacris crassicauda cambodiana ssp. nov., Eugryllacris serricauda sp. nov., Eugryllacris trabicauda sp. nov., Eugryllacris vermicauda sp. nov., Eugryllacris sulcata sp. nov., Eugryllacris inversa sp. nov., Gryllacris incornuta sp. nov., Gryllacris sok sp. nov., Gryllacris (Pardogryllacris) ovulicauda sp. nov., Gryllacris (Gigantogryllacris) bilineata sp. nov., Gryllacris (Gigantogryllacris) ligulata sp. nov., Lyperogryllacris forcipata sp. nov., Lyperogryllacris ocellata sp. nov., Lyperogryllacris khuntan sp. nov., Ocellarnaca disjuncta sp. nov., Ocellarnaca fusca sp. nov., Otidiogryllacris lawang sp. nov., Otidiogryllacris bamusbama sp. nov., Prosopogryllacris gamta sp. nov., Prosopogryllacris nigra sp. nov., Prosopogryllacris silacea sp. nov., Xanthogryllacris lineata sp. nov., Xanthogryllacris punctata sp. nov., Xanthogryllacris ralum sp. nov., Xanthogryllacris subrecta sp. nov., Aancistroger inarmatus sp. nov., Angustogryllacris bibulbata sp. nov., Aphanogryllacris sinustylata sp. nov., Aphanogryllacris nigritibiae sp. nov., Asarcogryllacris (Asarcogryllacris) brevis sp. nov., Asarcogryllacris (Asarcogryllacris) parapat sp. nov., Asarcogryllacris (Asarcogryllacris) robusta sp. nov., Asarcogryllacris (Pseudolarnaca) cornualis sp. nov., Asarcogryllacris (Pseudasarca) arborea sp. nov., Australogryllacris guttata sp. nov., Capnogryllacris (C.) erythrocephala fuscifrons ssp. nov., Capnogryllacris (C.) varifrons sp. nov., Capnogryllacris (C.) nigromaculata sp. nov., Capnogryllacris (C.) sakaerat toxica ssp. nov., Celebogryllacris brevitegmina sp. nov., Diaphanogryllacris annamita tenera ssp. nov., Diaphanogryllacris opulenta sp. nov., Diaphanogryllacris recta sp. nov., Diaphanogryllacris sinuata sp. nov., Eremus tigris sp. nov., Furcilarnaca chiangdao sp. nov., Furcilarnaca salit sp. nov., Furcilarnaca trilobata sp. nov., Haplogryllacris bilobulata sp. nov., Homogryllacris armigera sp. nov., Homogryllacris stabilis sp. nov., Larnaca (Larnaca) nigricornis sp. nov., Larnaca (Larnaca) tenuis sp. nov., Larnaca (Larnaca) samkos sp. nov., Larnaca (Larnaca) squamiptera sp. nov., Larnaca (Larnaca) subaptera sp. nov., Melaneremus sikkimensis sp. nov., Minigryllacris perpusilla sp. nov., Monseremus appendiculatus sp. nov., Neanias virens sp. nov., Neolarnaca vera nigrinotum ssp. nov., Phryganogryllacris extensa sp. nov., Phryganogryllacris gialaiensis fovealis ssp. nov., Phryganogryllacris nonangulata sp. nov., Siamgryllacris rufa sp. nov., Ultragryllacris pulchra nan ssp. nov., Ultragryllacris triangula sp. nov., Woznessenskia ampliata sp. nov., Woznessenskia bavi sp. nov., Zalarnaca (Glolarnaca) elegantula sp. nov., Zalarnaca (Glolarnaca) globiceps minor ssp. nov., Zalarnaca (Zalarnaca) maninjau sp. nov., Papuogryllacris diluta baiteta ssp. nov., Papuogryllacris rugifrons sp. nov., Papuogryllacris ligata bundi ssp. nov., Paraneanias striatus sp. nov., Plexigryllacris megastyla sp. nov. The following nomenclatural changes had to be done: Gryllacris bancana Karny, 1930a stat. nov. is raised to full species from subspecies of Gryllacris obscura Brunner von Wattenwyl, 1888; Xanthogryllacris inquinata (Karny, 1928c) comb. & stat. nov. is raised to full species from subspecies under Pardogryllacris dyak (Griffini, 1909); Eremus oberthuri Griffini, 1913a stat. nov. is raised to full species from subspecies under Eremus rugosifrons Brunner von Wattenwyl, 1888; Prosopogryllacris nigrovenosa (Karny, 1928b) stat. nov. is raised to full species from subspecies under Prosopogryllacris horvathi (Griffini, 1909); Xanthogryllacris punctipennis aurantiaca (Brunner von Wattenwyl, 1888) stat. reest. and Xanthogryllacris punctipennis dempwolffi (Griffini, 1909b) stat. reest. are treated as valid subspecies under Xanthogryllacris punctipennis (Walker, 1869) instead of being synonyms of the latter; Gryllacris thailandi Gorochov, 2007 and Gryllacris thailandi facemarmiger Gorochov et al., 2015 are downgraded to subspecies of Gryllacris vittata Walker, 1869. Gryllacris kledangensis Karny, 1923 and Gryllacris lombokiana Karny, 1926a become new synonyms of Gryllacris peracca Karny, 1923; Brachyntheisogryllacris abbreviata evolutior (Griffini, 1909a) becomes a new synonym of Brachyntheisogryllacris abbreviata (Brunner von Wattenwyl, 1888), and Haplogryllacris hieroglyphicoides (Chopard, 1924) a new synonym of Haplogryllacris simplex (Walker, 1871). The following new combinations are proposed: Capnogryllacris (C.) basaliatrata (Griffini, 1909c) comb. nov. from Cyanogryllacris Karny, 1937; Haplogryllacris aliena Walker, 1869 comb. nov. and Haplogryllacris durgensis (Gupta & Chandra, 2017) comb. nov. from Gryllacris Audinet-Serville, 1831; Homogryllacris artinii (Griffini, 1913b) comb. nov., Homogryllacris buyssoniana (Griffini, 1912c) comb. nov., Homogryllacris kurseonga (Griffini, 1913b) stat. & comb. nov. and Homogryllacris ? maindroni (Griffini, 1913a) comb. nov. from Brachyntheisogryllacris Karny, 1937; Larnaca (Larnaca) eugenii (Griffini, 1914b) comb. nov. from Metriogryllacris Karny, 1937; Larnaca (Larnaca) larnacoides (Karny, 1937) comb. nov. and Larnaca (Larnaca) jacobsoni (Griffini, 1913c) comb. nov. from Melaneremus Karny, 1937.